1/f Noise from Glauber Dynamics: Self-Consistent Interaction and Temperature Dependent Correlations - Amrit De (Advances in Condensed Matter Physics)
Low frequency flicker noise has been argued to occur in spatially extended metastable systems near a critical point (Bak et al., 1987). An Ising-Glauber model based method is suggested here to systematically obtain temperature dependent nth-order correlation functions for N arbitrary interacting two-level systems (TLSs). This model is fully consistent with existing methods to calculate 1/f noise spectra from TLSs and complements them. However, with as such no a priori assumptions on the typical log normal distribution of fluctuation rates, it is shown that 1/fα noise manifests in two different cases: first in the thermodynamic limit on a 2D lattice with long range antiferromagnetic interactions at low temperatures and second in the case of a statistical ensemble of finite-sized spin clusters representing disorder, but where each cluster is ordered due to ferromagnetic interactions.